10c+12c-16=-8

Simple and best practice solution for 10c+12c-16=-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10c+12c-16=-8 equation:


Simplifying
10c + 12c + -16 = -8

Reorder the terms:
-16 + 10c + 12c = -8

Combine like terms: 10c + 12c = 22c
-16 + 22c = -8

Solving
-16 + 22c = -8

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '16' to each side of the equation.
-16 + 16 + 22c = -8 + 16

Combine like terms: -16 + 16 = 0
0 + 22c = -8 + 16
22c = -8 + 16

Combine like terms: -8 + 16 = 8
22c = 8

Divide each side by '22'.
c = 0.3636363636

Simplifying
c = 0.3636363636

See similar equations:

| 3x^2+(2k-1)+12=0 | | -4k+7-2k=30 | | 7p=5p+p | | -19=10x+8-x | | 2.566x=-12.54774 | | 5+5y-5= | | x-5=3x-4 | | 30+3x+5x-5=145 | | 2b+7-3b=-5 | | -5+1/3a=-4 | | 4x^2-88x-92=0 | | 0.8x-7=2.3x-16 | | 2(3x-6)=2x+4 | | (x*x)+6x-5=0 | | -20x^2-14x-7=0 | | 6(2+3)+1+3-(-5)= | | 9-2c+6c=29 | | a+5=1/5(15+5a) | | 10x-(2)=-32 | | 2x-4+x+7=90 | | -9(x-5)+9=3x+42 | | 51-(3+6x-2(x+3))=5(4x-3)-(5(x-1)-16c+6) | | 6x=-16 | | -12+-3x=-12 | | 9+n=1+6n | | -4(1+3n)+7n=3(n-2)-6 | | -6-x+3=-4 | | 50000=20x-.001x^2 | | q-11=-5 | | 6/12-3/4 | | 2(7r-6)+6(6+5r)=24 | | 2(x+1)=-13-3x |

Equations solver categories